Drug Resistance Patterns of Bacterial Pathogens from Adult Patients with Pneumonia in Arba Minch Hospital, South Ethiopia (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: pneumonia; bacterial pathogens and antimicrobial susceptibility pattern